Changes in older persons’ lifestyle and perceived health over time and during the COVID-19 pandemic: findings from the extended follow-up of the FINGER randomized controlled trial from 2009 to 2020 - Jenni Lehtisalo; Maria Sääskilahti; Tommi Härkänen; Jenni Kulmala; Katri Hemiö; Sini Siltanen; Zhou Zhi; Francesca Mangialasche; Tiina Laatikainen; Timo Strandberg; Riitta Antikainen; Jaakko Tuomilehto; et al. (BMC Geriatrics)
Abstract Background Multidomain lifestyle trials have been shown to be effective in changing people’s behaviour during the intervention, but less is known about long-term effects of such interventions. The aim of this study was to investigate how self-reported lifestyle and self-evaluated health changed over a 10-year period in older adults participating in the FINGER randomised controlled trial. Effects of the initial lifestyle intervention and the COVID-19 pandemic on these behaviour changes were evaluated. Methods A two-year multicentre FINGER trial recruited community-dwelling people aged 60-77 years at risk of cognitive impairment (n=1259). Participants were randomised to a multidomain lifestyle intervention or regular health advice (control). They underwent study visits annually during the original trial period (at baseline, one, and two years) and twice during the follow-up (five and seven years), and responded to a survey during the COVID-19 pandemic at approximately 10 years. Generalised estimating equations (GEE) and linear mixed-effects regression model were used to analyse physical, cognitive, and social activity, food consumption, smoking, alcohol consumption, and self-evaluated health. Results People in the intervention group were better able to maintain their level of physical activity up to the five-year follow-up. The intervention group also improved their diet quality: difference in fish consumption was maintained up to the seventh year, and consumption of vegetables and fruits increased during the active intervention. Cognitive and social activities increased and self-evaluated health and memory improved during the active period, but decreased thereafter, without a group difference. During the COVID-19 pandemic, physical and cognitive activities increased. Conclusion Multidomain lifestyle intervention was beneficial for improving physical activity and healthy food choices in older people both in the short and long term, but had no effect on other activities, smoking, alcohol use, or self-evaluated health. Increased physical activity was the most evident pandemic-associated change in older adults’ lifestyle. Trial registration ClinicalTrials.gov, NCT01041989. Registered 04/01/2010 – Retrospectively registered, https://clinicaltrials.gov/ .